Analysis of Queuing at Theme Park Using Arena Simulation Software - Mohd Zainurin, Noor Syahidah Azim; Kamardan, Muhamad Ghazali (Enhanced Knowledge in Sciences and Technology, 2021)
This study focuses on the application of simulation in solving theme park queuing problem by using Arena software. The purpose of this study is to simulate queuing situation and to analyze the queuing at the theme park using the simulation result. Throughout this study, we analyze three variables such as average number of waiting (